Enhancement of the chondrogenic differentiation of mesenchymal stem cells and cartilage repair by ghrelin. Issue 6 (12th February 2019) - Fan, Litong; Chen, Jiaqing; Tao, Yanmeng; Heng, Boon Chin; Yu, Jiakuo; Yang, Zheng; Ge, Zigang
ABSTRACT: Transforming growth factor beta (TGF‐β) is commonly utilized in chondrogenic differentiation protocols, but this often results in incomplete maturation of the derived chondrocytes. Gene expression analysis, quantitation of sulfated glycosaminoglycan and collagen, and histological staining were performed to assess the effects of ghrelin. The signaling pathways involved were investigated with inhibitors or targeted by shRNAs. Joint cavity delivery of TGF‐β with or without ghrelin, within a rat cartilage defect model was performed to evaluate the in vivo effects of ghrelin. Ghrelin dramatically enhanced gene expression levels of SOX9, ACAN, and COL II and resulted in increased synthesis of sulfated glycosaminoglycan (sGAG) and collagen in vitro. Combined treatment with TGF‐β and ghrelin synergistically enhanced the phosphorylation of ERK1/2 and DMNT3A, which accounted for increased expression of chondrogenic genes. Delivery of ghrelin in combination with TGF‐β after MSC implantation within a rat osteochondral defect model significantly enhanced de novo cartilage regeneration, as compared to delivery with TGF‐β alone. In conclusion, ghrelin could significantly enhance MSC chondrogenic differentiation in vitro and can also enhance cartilage regeneration in vivo when used in combination with TGF‐β. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:1387–1397, 2019.